Reflexiones psicológicas sobre la educación y la sociedad peruana actual - Arboccó De los Heros, Manuel (2014)
In the following article a group ofpsychological and sociological reflectionsabout education, family, teaching andsociety subject. We believe that qualityand humanist education task in a complexand difficult context as the current mustnot paralyze us or demoralize, but rather,force us to find many ways to revert orimprove the national education reality ascan be possible.